Realization of broadband terahertz metamaterial absorber using an anti-symmetric resonator consisting of two mutually perpendicular metallic strips - Wang, Ben-Xin; Xu, Chongyang; Zhou, Haiquan; Duan, Guiyuan (APL materials, 2022)
This paper presents a scheme to achieve a broadband metamaterial absorber in the terahertz region, which is consisted of an anti-symmetric T-shaped resonator (formed by two mutually perpendicular metallic strips) on top of a metallic back layer separated by an insulator dielectric layer. The anti-symmetric T-shaped resonator can have a strong electromagnetic interaction with the incident beam, resulting in four different absorption peaks having adjacent frequencies, and the superposition effect of these adjacent peaks produces a broadband absorption. The resonance bandwidth of greater than 80% absorption can have 0.58 THz ranging from 1.54 to 2.12 THz, and its relative resonance bandwidth is 31.69%. The resonance bandwidth and relative resonance bandwidth can be scaled by controlling the parameters of two mutually perpendicular metallic strips in the anti-symmetric T-shaped resonator. Moreover, the parameter optimization of the anti-symmetric T-shaped resonator can realize five discrete absorption peaks with adjacent frequencies, and their combined effect can obtain not only broadband absorption but also a greater absorption bandwidth compared with the case of broadband absorption having four absorption peaks.